Efeito da paridade a longo prazo sobre a função da musculatura do assoalho pélvico - Bertacini, Daiane Munhoz Mira (2017)
Parity has been associated with an increase in risk of pelvic floor musculature dysfunctions. The aim of this study was to verify the effect of parity over this musculature in the long term. Materials and methods: A cross-sectional study accomplished at the Department of Physical Therapy, Federal University of São Carlos, Brazil. A hundred and forty three women participated in the study, grouped according to parity, between one and six years after the last delivery. The King’s Health Questionnaire was applied when the urinary complaint was confirmed, and the habitual physical activity was assessed by the “Baecke Habitual Physical Activity Questionnaire”. The function of the pelvic floor musculature was assessed through perineometry and unidigital vaginal palpation, using the PERFEC scheme, being the contraction graduation classified according to the Modified Oxford Scale. Results: In relation to the graduation of pelvic floor musculature contraction using the Modified Oxford Scale and perineometry, there was no significative difference in relation to parity (p=0.48) and (p=0.14) respectively. There was no statistical difference between groups referring to the current urinary incontinence complaint and in the domains of King’s Health Questionnaire. The regression analysis did not present a result that indicated the effect of parity in the variables analysed. Conclusion: it was not verified the effect of parity, regardless the mode of delivery, over the PFM function and presence of urinary symptoms, such as UI, in a period considered long term after birth.